PENGARUH STRATEGI PEMBELAJARAN SIMULASI DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SISWA SEKOLAH MENENGAH ATAS NEGERI 6 PEMATANG SIANTAR - Rusyadi Rusyadi (Universitas Islam Negeri Sumatera Utara Medan, 2018)
The objectives of this quasi experimental research were to discover applying whether:(1) the learning achievement of students’ Islamic eduction taught by applyingsimulation instructional strategy were higher than students’ learning achievement inIslamic education taught by applying expository instructional strategy, (2) the learningachievement of students’ Islamic education with high learning student independentthan the learning achievement of students’ Islamic education with low learningstudent independent, and (3) there was are an interaction between instructional strategyand learning student independentin affecting the learning achievement of students’Islamic education. The population of this study was all Grade XI students, StateSchool Six, Pematang Siantar regency, Based on cluster random sampling technique,one class was chosen to be taught by applying simulation instructional strategy danexpository strategy..The research findings releaved that: (1) on average the students’learning achievement taught by applying simulation instructional strategy X = 28.12higher than the average students’ learning achievement taught by applying expositorylearning strategy X = 27.00 with Fcount = 113.96 > Ftable = 3.984, (2) on average thestudents’ learning achievement with high learning student independent was X = 29.61higher than the learning learning student independent with low X = 25.93 with Fcount =7.66 > Ftable = 3.984, and (3) there was an interaction between instructional strategyand learning learning student independent toward learning achievement in Islamiceducation with Fcount = 35.48 > F table = 3.984.